DNA Damage among Wood Workers Assessed with the Comet Assay - Evin Danisman Bruschweiler; Pascal Wild; Cong Khanh Huynh; Dessislava Savova-Bianchi; Brigitta Danuser; Nancy B. Hopf (SAGE Publishing, 2016)
Exposure to wood dust, a human carcinogen, is common in wood-related industries, and millions of workers are occupationally exposed to wood dust worldwide. The comet assay is a rapid, simple, and sensitive method for determining DNA damage. The objective of this study was to investigate the DNA damage associated with occupational exposure to wood dust using the comet assay (peripheral blood samples) among nonsmoking wood workers ( n = 31, furniture and construction workers) and controls ( n = 19). DNA damage was greater in the group exposed to composite wood products compared to the group exposed to natural woods and controls ( P < 0.001). No difference in DNA damage was observed between workers exposed to natural woods and controls ( P = 0.13). Duration of exposure and current dust concentrations had no effect on DNA damage. In future studies, workers' exposures should include cumulative dust concentrations and exposures originating from the binders used in composite wood products.